Part I : Highly enantioselective intermolecular alpha-alkylation of aldehydes with activated alcohols. Part II : Copper-catalyzed stereo- and enantioselective systhesis of organosilanes - Zhao, Kai (2015)
The catalytic enantioselective and/or stereoselective carbon-carbon bond forming reactions have blossomed rapidly over the past few decades because of their substantial utility in constructing a multitude of biologically and pharmaceutically important molecules. In this context, this thesis mainly focuses on the study of catalytic enantio- and/or stereoselective carbon-carbon bond forming reactions, which contains two parts: Part I focuses on the highly enantioselective intermolecular α-alkylation reaction of aldehydes with activated alcohols: In chapter 1, we demonstrated a highly enantioselective α-alkylation reaction of aldehydes with activated alcohols by employing a cooperative catalytic system consisting both Brønsted acid and diarylprolinol silylether, affording a variety of α-alkylated aldehydes with excellent enantiocontrol. In chapter 2, we developed an acid-free asymmetric α-alkylation of aldehydes employing a fluorinated alcohol TFE as the solvent, forging enantioenriched products without the addition of any external Brønsted or Lewis acids. Part II focuses on the copper-catalyzed stereo- and enantioselective synthesis of organosilanes: In chapter 3, we introduced a regio- and stereoselective silylation of α,β-acetylenic carbonyl compounds with Me2PhSi–Bpin catalyzed by CuCl/NaOtBu/xantphos system via the activation of Si–B bond, affording a plethora of synthetically important β-silyl-α,β-unsaturated carbonyl compounds in good yields and excellent E/Z selectivities. In chapter 4, an overview of the recently reported synthetic methods for the preparation of enantioenriched β-silyl carbonyl compounds has been given. In chapter 5, we demonstrated a highly efficient asymmetric conjugate addition of Grignard reagents to β-silylenoates catalyzed by CuI/(R)-Tol-BINAP system, which provided an attractive, practical and concise route to various alkyl-substituted enantioenriched β-silylesters. The potential synthetic values of this methodology have been highlighted through a plethora of tranformations granted to β-hydroxyl ester, allylic silanes as well as various enantiopure organosilanes bearing multiple stereogenic centers. In the appendix, we demonstrated a copper-catalyzed regio- and stereoselective olefinic arylation of acyclic enamides with diaryliodonium salts. The reactions were performed under very mild conditions to give a variety of E-configured β-arylated enamides in moderate to good yields.